Mutant Lef1 controls Gata6 in sebaceous gland development and cancer. (18th March 2019) - Oulès, Bénédicte; Rognoni, Emanuel; Hoste, Esther; Goss, Georgina; Fiehler, Ryan; Natsuga, Ken; Quist, Sven; Mentink, Remco; Donati, Giacomo; Watt, Fiona M
Abstract: Mutations in Lef1 occur in human and mouse sebaceous gland (SG) tumors, but their contribution to carcinogenesis remains unclear. Since Gata6 controls lineage identity in SG, we investigated the link between these two transcription factors. Here, we show that Gata6 is a β‐catenin‐independent transcriptional target of mutant Lef1. During epidermal development, Gata6 is expressed in a subset of Sox9‐positive Lef1‐negative hair follicle progenitors that give rise to the upper SG. Overexpression of Gata6 by in utero lentiviral injection is sufficient to induce ectopic sebaceous gland elements. In mice overexpressing mutant Lef1, Gata6 ablation increases the total number of skin tumors yet decreases the proportion of SG tumors. The increased tumor burden correlates with impaired DNA mismatch repair and decreased expression of Mlh1 and Msh2 genes, defects frequently observed in human sebaceous neoplasia. Gata6 specifically marks human SG tumors and also defines tumors with elements of sebaceous differentiation, including a subset of basal cell carcinomas. Our findings reveal that Gata6 controls sebaceous gland development and cancer. Synopsis: Transcription factor Lef1 has been linked to de novo formation of sebaceous glands and related skin tumors via unclear mechanisms. Here, genetic work combined with lineage tracing identifies a β‐catenin‐independent link between mutant Lef1 and Gata6 in the regulation of sebaceous gland morphogenesis, lineage identity and tumorigenesis. Gata6‐positive progenitors emerge during hair follicle morphogenesis and generate the upper part of the sebaceous gland. Gata6 is a direct transcriptional target of N‐terminally truncated Lef1 (ΔNLef1) in K14ΔNLef1 mice, which exhibit expansion of the upper pilo‐sebaceous compartment and spontaneous sebaceous tumors. Gata6 is expressed in murine and human sebaceous tumors and is mutated in some human sebaceous carcinomas. Gata6 upregulates the DNA mismatch repair pathway, thereby exerting tumor suppressor activity. Abstract : Genetic work combined with lineage tracing analyses reveals a link between mutant Lef1 and Gata6 in the formation of sebaceous glands and associated tumors.